PERBEDAAN KUALITAS HIDUP BERDASARKAN SHORT FORM36 ANTARA PENDERITA STROKE ISKEMIK SERANGAN PERTAMA DENGAN KEDUA - Nazwan Hassa,* Jimmy Eko Budi Hartono,* Dwi Pudjonarko* (NEURONA, 2017)
INTRODUCTION STROKE IS THE BIGGEST CAUSE OF PHYSICAL DISABILITY EMOTIONAL AND SOCIAL LIFE IN ADULTS THE RECURRENT STROKE LET TO DECREASED THE QUALITY OF LIFE